Percepções de pais/mães de autistas que praticam equoterapia em relação ao cuidado no viver-envelhecer - Mello, Paulo Cezar (2021)
This study aimed to understand the benefits of hippotherapy in relation to care in living-aging from the perception of parents of autistic children. And to support this objective, the following specific objectives were obtained: to know the benefits identified by fathers/mothers in the care linked to participation in horse-assisted therapy and; identify potentialities and difficulties related to the participation of children in horse-assisted therapy. The work is organized into three sections: scientific production I, II and III. The first production aimed to understand the perception of those responsible for people with autism about participation in horse-assisted therapy in relation to living-aging. The second production aimed to understand the perception of fathers/mothers of individua ls with Autistic Spectrum Disorder regarding participation in horse-assisted therapy. These two productions are a qualitative, exploratory-descriptive study, with a cross-sectional design, carried out with sixteen fathers/mothers and/or guardians of individuals with autism who participate in an Extensionist Project in Riding Therapy at the University of Passo Fundo. Data were collected from November to December 2020, conducted through individual interviews, from a semi-structured questionnaire, the speeches of the participants were systematized and coded using the NVivo ®10 software, following the assumptions of thematic content analysis of Bardin, who generated categories of similarities and correlations. Once the coding process was completed, it was possible to generate three categories (nodes) in each of the productions. The results presented evidenced the importance of regularity in the hippotherapy sessions, the relationships established in the sessions between practitioner-horse developing quality and affection, passing to gains in self-esteem and safety, followed by motor improvements and in the sense of limits and autonomy. In addition, the advance in sociability and relationships, with improvements in anxiety and independence and, in relation to the difficulties facing the Covid-19 pandemic, it was reported that the interruption of hippotherapy interventions caused anxiety crises, causing breaks in the routine in the lives of practitioners. The third production aimed to reflect on the importance of hippotherapy in the living-aging of individuals with autism from an extension project in hippotherapy. This production is based on hippotherapy, the relationship with care, the definition of Autistic Spectrum Disorder and the process of living-aging. Encouraging interaction with individuals, through collective activities, such as hippotherapy, brings benefits for a healthy aging of the mind and body of practitioners.